Curriculum and Practice for Children's Contextualized Learning - Jilin, Li (Springer Berlin Heidelberg, 2018)
Based on the authors' over 30 years of practical research experience, this book shows how situation curriculum design illustrates the new idea of "combining subject curricula with children's activities." Particular attention is given to the subject curriculum, activity curriculum and the optimization of the situation. The curriculum is the most important vehicle of children's learning, and the primary school curriculum is vital to children's growth. Drawing on detailed case studies, the book highlights how situation curriculum design is currently affecting traditional Chinese primary schools.